ПОДГОТОВКА УЧЕБНОЙ ПРОГРАММЫ ПО УПРАВЛЕНИЮ ГОСУДАРСТВЕННЫМ СЕКТОРОМ НА ФИЛИППИНАХ В СООТВЕТСТВИИ С ТРЕБОВАНИЯМИ XXI ВЕКА - Акино-младшийПерфекто; Джалагат-младшийРевенио (Вопросы государственного и муниципального управления, 2021)
The UNESCO World Conference on Higher Education, held in Paris, France in October 1998, adopted a universal declaration on the need for a new vision and paradigm in higher education responsive to the challenges of the 21st century. This study is an effort to answer this call but only in the limited field of public sector management education curriculum at the Master’s level. This study attempted an evaluation of existing curricula in terms of the responsive objectives in knowledge, skills, and values as well as the perceived gap between theory and practice. Further, it sought to identify any differences among school administrators, faculty, and students including practitioners in their perceptions regarding these objectives. The study used a three-staged survey to surface data as basics for the proposed curriculum. The first stage was a request for printed materials of the Master in Public Administration/counterpart courses from 66 educational institutions. The second stage was a questionnaire to which 69/132 (52%) school administrators, 112/198 (56.5%) faculty, 188/330 (56.9%) students, and 76/76 (100%) are practitioners, representing an overall 60.4 percent retrieval rate. The questionnaires sought answers to the specific sub-problems of the study. The third questionnaire was sent to all respondents who replied to the second questionnaire; their opinion on the proposed objectives and courses/subjects were sought. Based on the findings, the researchers developed the proposed curriculum. This curriculum in conformity with the Commission on Higher Education standards consists of the following: 1. Core/Professional Orientation (12 units), Theory and Practice of Governance (3 units), Human Behavior in Organization (3 units), Leadership and Organization Change (3 units), Administrative Laws (3 units); 2. Research and Evaluation (6 units), Quantitative Methods of Management and Statistics (3 units), Research Techniques (3 units); 3. Major Subjects (15 units) on any of the following: Economic Development (3 units), Development Administration (3 units), Communication and Information Management (3 units), Public Management Issues (3 units), Ethics and Accountability in the Public Service (3 units), Environmental Management (3 units); 4. Thesis Writing (6 units). This study will be useful to schools or will offer a public sector management education course at the Master’s level as well as to the Commission on Higher Education for standard setting.